57 The impact of preoperative renal dysfunction and therapy type in patients with type 2 diabetes undergoing coronary artery bypass surgery. (9th June 2011) - Menon, A; Hodson, J; Pagano, D; Mascaro, J; Wilson, I C; Rooney, S J; Graham, T R; Bonser, R S
Abstract : Introduction: There is limited data addressing the impact of preoperative renal dysfunction in type 2 diabetics (T2DM) undergoing first-time coronary artery bypass surgery (CABG); specifically exploring the influence of diabetic management (oral hypoglycaemic (OH) and insulin therapy (IN)). We assessed the impact of preoperative renal status and diabetic management on the post operative renal status, morbidity, 30-day and long-term survival in T2DM-CABG. Methods: We reviewed prospectively accrued data from 1/1/1999 to 31/12/2009. Pre and 4 to 5-day postoperative creatinine clearance (CrCl) was calculated using Cockcroft-Gault formula. Patients were subgrouped into 5 grades based on preoperative CrCl; Group I CrCl≥90 ml/min; II 60–89; III 30–59; IV 15–29; V <15 or haemodialysis. Late Kaplan–Meier survival data (compared by log rank method), censored at 1/10/2009 were obtained from the UK CCAD. Surgical morbidity outcomes included re-exploration for bleeding, stroke (type 1 deficit) and low cardiac output state (LCOS) requiring inotropes ± intra-aortic balloon counterpulsation were compared using Fisher's Exact tests. Results: 1215 patients (921 males) with a mean age of 64 years (31–89 years) underwent CABG; 742 on OH and 472 on IN. Preoperative renal status in the groups were Group I -209(17%), II-584(48%), III-387(32%), IV-26(2%) and V (8(1%). Similar percentages in each group had ≥1 grade deterioration of renal function postoperatively 19%, 18%, 16% and 23% (grades I–IV respectively; p=0.470). When examined as a continuous variable, higher preoperative CrCl correlated with a better postoperative improvement in CrCl (r=0.073, p=0.012 Spearman Rank). Overall 30-day mortality was 3.33% (CI 2.32 to 4.34%) and was not different by group I-3.37% (CI 0.92 to 5.82), II-2.09% (CI 0.92 to 3.26%), III 4.92% (CI 2.76 to 7.08%), IV 8% (CI 0 to 18.6%) and Stage V 0% (CI 0 to 0.4%; p=0.101) or by therapy type; (p=0.411). IN patients had similar preoperative renal function (median CrCl 66.8 vs 68.6; p=0.828) but a higher rate of postoperative renal deterioration (53.3 vs 46.7%, p<0.001). Stroke (p=1.000), bleeding (p=0.755) and LCOS (p=0.335) incidence were not different between therapy type. Overall mean survival was 9 years (CI 8.7 to 9.2 years) and was not different by renal function grade (p=0.612). However, IN patients had shorter mean survival 8.7(8.3 to 9.0) vs OH 9.1(8.8 to 9.4) years; p=0.03. Conclusions: In T2DM-CABG, 36% of patients have CrCl <60 ml/min. Higher CrCl protects against postoperative renal deterioration. Renal dysfunction does not appear to affect hospital outcome or survival. However, preoperative IN requirement increases the risk of renal dysfunction and is associated with worse longer-term survival.